Exploring regulations and scope of the Internet of Things in contemporary companies: A first literature analysis - Giuseppe Russo; Bruno Marsigalia; Federica Evangelista; Matteo Palmaccio; Marina Maggioni (Journal of Innovation and Entrepreneurship, 2015)
Purpose: The Internet of Things is the networked connection of people, processes, data and things, which together are able to achieve more relevant and valuable connections than ever before. In this framework, every aspect of economic and social life will be related via sensors and software to an Internet of Things platform, and the resulting data continuously flow into big data at every node. In order to provide a better understanding of this smart infrastructure, the aim of this paper is to investigate the Internet of Things through a revised theory of the topic, examining the period from 1985 to 2015, with the purpose of identifying the new opportunities offered by the Internet of Things to the economic-system and learn how to manage them. Design/methodology/approach: The Internet of Things was analysed by applying a qualitative method with a single method approach to the existing literature. We developed the research by studying national and international literature and, by running four key words (Internet of Things, Energy Internet, Communications Internet and Logistics Internet) through two databases (Google Scholar and EBSCO), we obtained a range of scientific contributions that could complement the literature review. The research sources are of a secondary nature. Originality/value: The Internet of Things can connect everything to everyone in an integrated global network. This network promises efficiency and social and individual benefits by quantifying and monitoring previously measureless qualities. The analysis of the literature review on the Internet of Things is, therefore, a way to fully appreciate the characteristics, opportunities, possible applications, risks and potential issues linked to the topic. Practical implications: Through our theory, our aim is to contribute towards identifying the main features, fields of application and corresponding potential applications for the Internet of Things, offering new ideas for further analysis.
Keywords: 650; Big data; Internet of Everything; Internet of Things; Logistics Internet; Communication Internet; Energy Internet; Companies